Balloon-occluded transcatheter arterial chemoembolization using miriplatin for hepatocellular carcinoma - Toyoda, Mitsuo; Takizawa, Daichi; Arai, Hirotaka; Kobayashi, Takeshi; Takayama, Hisashi; Nagashima, Tamon; Abe, Takehiko (Kanzo, 2013)
The efficacy and safety of balloon-occluded transcatheter arterial chemoembolization (B-TACE) using miriplatin were investigated in 26 patients with hepatocellular carcinoma, and compared with conventional TACE (C-TACE). In the B-TACE group, a treatment effect (TE) of 4 was obtained in 61.5%, TE3 in 34.6%, TE2 in 3.8%, and TE1 in 0%. In the C-TACE group, the respective results were 44.2%, 34.6%, 19.2%, and 1.9%. Efficacy was significantly higher in the B-TACE group. There were no significant differences in the incidence of adverse events of grade 3 or more severe between the two groups. B-TACE using miriplatin is more useful than C-TACE, and B-TACE is as safe as C-TACE.